The Camorra in the South Pontine: the story of a casalese settlement in a contiguous, non-traditional area (Rivista di Studi e Ricerche sulla criminalità organizzata, 2024)
The article aims to analyse the criminal mafia settlement in the lower Lazio region, in particular in Formia town. Starting from a historical reconstruction, the work identifies the criminal and contextual factors that have favored the movement of Camorra clans and have contributed to their subsequent establishment. The study reported in the article is grounded on media, judiciary, and oral sources.
Keywords: Camorra; non–traditional areas; mafia movement; Formia